2013
DOI: 10.1371/journal.pone.0077972
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat Interacts with and Regulates the Localization and Processing of Amyloid Precursor Protein

Abstract: HIV-1 Tat protein plays various roles in virus proliferation and in the regulation of numerous host cell functions. Accumulating evidence suggests that HIV-1 Tat also plays an important role in HIV-associated neurocognitive disorders (HAND) by disrupting intracellular communication. Amyloid beta (Aβ) is generated from amyloid precursor protein (APP) and accumulates in the senile plaques of Alzheimer's disease patients. This study demonstrates that Tat interacts with APP both in vitro and in vivo, and increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 70 publications
4
51
1
Order By: Relevance
“…Tat increases Aβ secretion in neuron cultures [187]. Injection of lentiviral Tat construct into the hippocampus of mice results in elevated levels of Aβ production and increases the size and number of Aβ plaques [190]. Moreover, Tat further increases the burden of Aβ in AβPP/PS1 mice crossed with HIV-1Tattransgenicmice[191].…”
Section: Contribution Of Hiv Viral Proteins and Cart To The Developmementioning
confidence: 99%
See 1 more Smart Citation
“…Tat increases Aβ secretion in neuron cultures [187]. Injection of lentiviral Tat construct into the hippocampus of mice results in elevated levels of Aβ production and increases the size and number of Aβ plaques [190]. Moreover, Tat further increases the burden of Aβ in AβPP/PS1 mice crossed with HIV-1Tattransgenicmice[191].…”
Section: Contribution Of Hiv Viral Proteins and Cart To The Developmementioning
confidence: 99%
“…Tat also binds to heparan sulfate proteoglycan receptors on the microglia surface and decreases the transfer of Aβ to LRP1, thereby inhibiting phagocytosis [193]. Tat enhances Aβ burden by promoting the accumulation of AβPP into lipid rafts [190]. Tat and peptides derived from Tat decrease the activity of neprisylin, a major Aβ-degrading enzyme [187, 194].…”
Section: Contribution Of Hiv Viral Proteins and Cart To The Developmementioning
confidence: 99%
“…Insulin degrading enzyme (IDE) or neprilysin can proteolyze Aβ42 and prevent deleterious Aβ42 aggregations in neurons (Madani et al 2006). In order to evacuate Aβ42 from neural tissue, active shuttling of Aβ42 from the brain into the bloodstream occurs through receptors for advanced glycation end-products (RAGE) and lipoprotein 1 receptors (LRP1) located on endothelial cells in the brain vasculature (Hickman et al 2008; Kim et al 2013). Altogether these systems help regulate Aβ42 levels in a sustainable balance that is necessary for normal cellular metabolism.…”
Section: Multiple Amyloid Synthesis and Degradation Pathways Exist Inmentioning
confidence: 99%
“…While the current diagnostic value of CSF and 11 C-PiB measurements of amyloid remain less clear for HIV compared to AD, many in-vitro studies still suggest that neuro-inflammation, as seen with HIV, can affect amyloid metabolism (Kim et al 2013a). A promising method to investigate differences is CSF proteomics.…”
Section: Recent Advances In Csf Biomarkers Proteomics and Neuroimagmentioning
confidence: 99%
“…Similarly, astrocytic tumor growth factor β-mediated neuroprotection was demonstrated in a mouse model for subacute neuroinflammation (Cekanaviciute et al , 2014). Although deleterious effects of intracellular accumulation of amyloid beta (Aβ) is well known in AD, a recent study using an amyloid precursor protein/presenilin-1 transgenic mouse model revealed that HIV-1 Tat can contribute to HAND by modifying amyloid precursor protein processing to increase Aβ production (Kim et al , 2013). …”
Section: Aeg-1 In Handmentioning
confidence: 99%